2018
DOI: 10.3390/ma11102060
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Laser Transmission Welding of Glass with Titanium Alloy by Laser Surface Treatment

Abstract: Laser surface treatment of the titanium alloy was locally oxidized on the metal surface to improve the joint strength of laser transmission welding of high borosilicate glass with titanium alloy. The results find that the welding strength was increased 5 times. The welding mechanism was investigated by the morphology of the welded parts, the tensile-fracture failure mode, the diffusion of the interface elements, and the surface free energy. The results show that there are many adherents between the titanium al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Their proposed solution involves using a femtosecond laser to join Al6082 and SiO2, aiming to reduce material surface roughness and enhance bonding strength. Li et al [7] contributed to improving joint strength in laser transmission welding by validating a laser surface treatment for titanium alloy. Their approach, involving local oxidation of the metal surface, resulted in a significant fivefold increase in welding strength when joining high borosilicate glass with titanium alloy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their proposed solution involves using a femtosecond laser to join Al6082 and SiO2, aiming to reduce material surface roughness and enhance bonding strength. Li et al [7] contributed to improving joint strength in laser transmission welding by validating a laser surface treatment for titanium alloy. Their approach, involving local oxidation of the metal surface, resulted in a significant fivefold increase in welding strength when joining high borosilicate glass with titanium alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Their analysis, utilizing scanning electron microscopy and x-ray diffraction, revealed that the joining mechanism primarily involved mechanical mixing between the two materials. Ji et al [7] demonstrated innovative laser welding of dissimilar glass and Kovar without optical contact. Their results showed that a femtosecond laser irradiated the Kovar alloy's surface, generating micro/nano particles that created strong adhesion between the two materials.…”
Section: Introductionmentioning
confidence: 99%
“…Akihiro Utsumi et al used an Nd:YAG laser with wavelength of 532 nm and pulse width of 5 ns to weld borosilicate glass and copper [3]. Pin Li et al used an Nd:YAG laser with wavelength of 1064 nm and pulse width of 2.5 ms to weld laser treated titanium alloy and high-borosilicate glass [14]. These studies demonstrated the feasibility of welding glass and metal using nanosecond or longer pulse lasers.…”
Section: Introductionmentioning
confidence: 99%
“…They achieved a high shear strength of bonding, measuring 8.94 MPa. Li et al [20] successfully conducted laser transmission welding of high borosilicate glass with titanium alloy using an Nd:YAG laser with a pulse width of 2.5 ms. Utsumi et al [7] employed a nanosecond laser system and successfully weld borosilicate glass and copper. They obtained the maximum shear strength of the bond was 690 kPa according to a pulse energy of 300 µJ.…”
Section: Introductionmentioning
confidence: 99%